An evaluation of day-care workers' skill in guiding young children towards literacy a basis for training programs - Pareja, Teresita P. (2008)
The study aimed to evaluate the strengths and weaknesses of the day-care workers in teaching beginning reading among children enrolled at day-care centers. Likewise, the study also included the performance of the day care workers in teaching children development since the former and literacy are inseparable. More importantly, the study also aimed to develop a training program that will address the weaknesses of the day-care workers in guiding young children towards literacy. This study will not only benefit the day-care workers, but also the children who will be under their care.
The research made use of an evaluation research design. The evaluation research focused on the formative evaluation of the performance of Day-Care Workers at Tanza, Cavite in guiding children towards literacy. The formative evaluation was backed up with descriptive research research because the needs analysis regarding the teaching of beginning reading required a survey through the use of questionnaire and focus group discussion. Through a complete enumeration, the study involved 32 day-Care Workers of Tanza, Cavite for 36 Day-Care Centers. In collecting data, the study made use of modified survey questionnaires, focus group discussion (FGD), classroom observation and field note.
In order to analyze and interpret the data gathered, the study used mean and percentile as its statistical instruments.
Based on the analysis of the data, the study revealed that day-care workers' strengths are on classroom management, inculcation of values, disciplining children, and on planning. On the contrary, the study revealed that they do not have enough knowledge in teaching children phonemic awareness, alphabetic understanding and phonological/alphabetic code or the ability to translate fluently the letters to sounds to words despite the fact that they are up-to-date with the curriculum, teaching practices and strategies in developing children and teaching literacy. Thus, this implies that the training program should be based on these weaknesses.
The results of the study prove that day-care workers play vital roles in developing children as well as in guiding them towards early literacy.
Realizing the tasks of the day-care workers, the local government must provide monthly salary to day-care workers and not only an honorarium. Likewise, it is also important to note the important role of Barangay Captains in supporting the day-care centers in terms of their physical structure and equipment or materials to be used by the children. Barangay Captains must be supportive financially to all day-care centers.
Keywords: Day-Care Workers